Gender Equality and Family Harmony in the Qur'anic Perspective - M Djidin (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
This study explores gender equality within the family from a Qur’anic perspective, emphasizing that the marital relationship should be rooted in justice, compassion, and cooperation. Employing a qualitative method, the research examines key Qur’anic verses, including those from Surah An-Nisa and Al-Baqarah, alongside interpretations from classical scholars, such as Al-Qurtubi, and contemporary thinkers like Sayyid Qutb, Muhammad Abduh, Ibn Ashur, M. Rashid Rida, Hamka, and M. Quraish Shihab. The findings reveal that the husband’s role as family leader is a moral obligation grounded in responsibility, rather than authority or domination. Similarly, the wife’s role in child-rearing and maintaining emotional stability is highlighted as vital to fostering household harmony. Together, these roles are presented as complementary, ensuring balance and mutual respect within the family. This research provides insights into establishing adaptive, sustainable households that promote both individual well-being and societal stability. By offering a framework for harmonious family life, it contributes to broader discussions on gender equality and its role in fostering social cohesion.